HATHA-YOGA AS MEANS OF PRENATAL PHYSICAL CULTURE IN CONDITIONS OF HEALTH PRESERVATION - Минникаева, Наталья Викторовна; Сапего, Анна Викторовна; Игишева, Людмила Николаевна (Mother and Baby in Kuzbass, 2017)
Review is devoted to the influence of prenatal physical activities on the body of a pregnant woman. The main means of prenatal physical culture and forms of physical activity are reviewed. The present scientific understanding of the use of yoga as a means of physical training to ensure the harmonious development of the individual at different stages of ontogenesis are stated. The peculiarities of planning and carrying out of hatha-yoga classes, depending on the gestational age of women are revealed.